(untitled) (Indian Journal of Child Health, 2020)
Background: Timely diagnosis of critical congenital heart disease (CrCHD) is challenging but critical. Although echocardiography is the gold standard for diagnosis of CrCHD, it cannot be used as a screening tool. Pulse oximetry is a non-invasive, cost-effective screening tool, which can be used to detect CrCHDs in newborns. Objective: The main objective of the study was to assess the usefulness of pulse oximetry as a screening tool for early detection of CrCHD in otherwise asymptomatic newborns. Materials and Methods: This study was a hospital-based prospective observational study carried out at the Department of Paediatrics at a Tertiary Hospital of Southern India over a period of 12 months from January 2016 to December 2016. A total of 1000 asymptomatic newborns of >35 weeks of gestation born in the hospital were enrolled in the study. The screening was considered positive if pulse oximetry saturation (SpO2) <90% in right hand (RH) or foot (F) or three readings of SpO2 of 90–94% in RH and F or >3% SpO2 difference between RH and F at three readings. Echocardiography was performed in those with clinical suspicion of CHD and/or positive pulse oximetry screening. Results: In the present study, the sensitivity of pulse oximetry for detection of CrCHD was 100% and specificity was 98.5%. Conclusion: Pulse oximetry screening is an effective and reliable test which significantly increases the detection rate of CrCHDs compared to the current practice of clinical examination alone as a screening tool. This study reinforces the importance of pulse oximetry screening in newborns.